Butterfly Diversity and Community Dynamics in the Central Himalayas: Species Composition, Richness, Abundance, and Seasonal Variation of Butterflies (Lepidoptera: Papilionoidea) in Bhorletar, Nepal - Sajan KC; Anisha Sapkota (Ecology and Evolution, 2024)
ABSTRACT Butterflies are among the most effective bioindicators of climate change; however, their diversity in many rural areas of the Central Himalayas remains understudied. This study provides an assessment of butterfly diversity in the foothills of Bhorletar, Madhya Nepal Municipality, Lamjung District, Nepal, within an elevation range of 420–600 m. Conducted between July 2019 and January 2021, the survey involved opportunistic observations and photography of adult butterflies in their natural habitats, with sampling occurring six times each month. The study aimed to investigate the species composition, richness, and abundance of butterflies across the survey period and identify seasonal changes in species composition and richness. A total of 94,009 individuals across 226 species, 129 genera, and six families were documented. During this study, Halpe arcuata Evans, 1937 and Hasora taminatus bhavara Fruhstorfer, 1911 were recorded for the first time in Nepal. Additionally, Halpe filda Evans, 1949 and Ctenoptilum vasava vasava (Moore, [1866]) were recorded for only the second and third times, respectively, in Nepal, following a gap of approximately three decades. The most abundant species was Pieris canidia indica Evans, 1926 (Relative Abundance [RA] 2.55%), followed by Pseudozizeeria maha maha (Kollar, [1844]) (RA 2.13%). Species richness showed an annual bimodal distribution, peaking in April (180 species) and August (161 species), while the lowest richness was observed in January and February, with 68 and 75 species, respectively. Diversity indices included a Shannon–Wiener index of 4.71, Pielou's J index of 0.87, an effective number of species of 111.24, and Margalef's richness index of 19.65, indicating high species diversity with a well‐balanced mix of species evenness and richness. This study offers the first peer‐reviewed checklist of butterflies from Bhorletar, providing crucial baseline data for future research and conservation efforts, and highlights the remarkable seasonal and species diversity within the region.